Highly compact refractive index sensor based on stripe waveguides for lab-on-a-chip sensing applications - Perera, Chamanei; Vernon, Kristy; Cheng, Elliot; Sathian, Juna; Jaatinen, Esa; Davis, Timothy (Beilstein Journal of Nanotechnology, 2016)
In this paper we report the design and experimental realisation of a novel refractive index sensor based on coupling between three nanoscale stripe waveguides. The sensor is highly compact and designed to operate at a single wavelength. We demonstrate that the sensor exhibits linear response with a resolution of 6 × 10−4 RIU (refractive index unit) for a change in relative output intensity of 1%. Authors expect that the outcome of this paper will prove beneficial in highly compact, label-free and highly sensitive refractive index analysis.
Keywords: interferometer; sensing; surface plasmons; waveguides